GELLAN GUM, A SPHINGOMONAS MICROBIAL POLYSACCHARIDES: BIBLIOMETRIC ANALYSIS OF TRENDS AND APPLICATIONS - Fahmi Achmad Saputra; Indria Puti Mustika; Tiolita, Fitriana; Rudiyono (BRIN Publishing (Penerbit BRIN), 2024)
Bacterial polysaccharides have gained considerable interest in recent years because of their wide range of applications. Gellan gum (GG) is a biodegradable microbial exopolysaccharide that has a wide range of commercial applications due to its versatility. Although GG is being used more frequently, research on it continues to evolve. This study used bibliometric analysis to examine patterns in GG application research over the last four decades. The data were obtained from the Scopus database, and the study of performance was carried out using R-Studio Biblioshiny. The important factors that were evaluated included the type of documents, the annual trends in publication, the subject areas covered, the titles of the journals, the analysis of citations, the distribution of countries, and the analysis of keywords. A total of 714 documents associated to GG were found, with articles being the most common document type. There has been a significant increase in research on GG applications since 2009. China became the primary provider, but the United States showed substantial participation in international collaborations. VOSviewer was used to show the co-authorship between countries and the co-occurrence of keywords in the field of GG research, emphasizing the predominant concentration on biomedical topics. The findings suggest that emergent research trends are primed for additional industrial growth.